Non-tuberculous Mycobacterial Pulmonary Disease: an Italian National Survey - Del Prato, Bruno; Altieri, Alfonso Maria; Carlucci, Biagio; Mori, Pier Anselmo; Parrella, Roberto; Stainer, Anna; De Giacomi, Federica; Pesci, Alberto; Faverio, Paola; Gruppo di Studio AIPO, on behalf of (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
The incidence of non-tuberculous mycobacteria (NTM) infection is increasing in Europe. However, a picture of Italian epidemiology and clinical practice is missing. We performed a national Italian survey involving 42 respiratory medicine departments. The NTM species more frequently isolated were Mycobacterium avium complex, followed by M. xenopi and M. kansasii. Patients with NTM were more frequently female (57%), and over 60 years of age, with bronchiectasis and COPD as main comorbidities. Bronchoscopic samples were widely used in the diagnostic phase. Of all patients with NTM, 73% met the criteria for NTM pulmonary disease. Despite strong adherence to the guidelines, physicians found significant difficulties related to pharmacological adverse events, patients’ compliance and poor outcomes.